Review on challenges among small and medium enterprises in Malaysia - Lohana, Sonia Shanker; Mohamed Zabri, Shafie; Ahmad, Kamilah (American Scientific Publishers, 2018)
Small and Medium Enterprises (SMEs) have been considered as a backbone for economy both in developed and developing countries. SMEs play significant role in the growth of economy of every country due to their vital contributions towards GDP and employment. The main drive of this paper was on the competiveness of the SMEs in Malaysia. In addition, this paper also seek to explore the definition of SMEs and also further explore the challenges facing SMEs. Apart from these, this paper also offers some possible solutions to the challenges faced by the SMEs. This paper add to the knowledge and the familiarity about the current issues relating to the SMEs in Malaysia. In brief, challenges faced by the SMEs in Malaysia can be summarized as the imperfect capability to meet the market environment, limited capacity for technology management, knowledge acquisition, lack of skilled human resources and also limited access to finance and capital. However, SMEs across different sizes was found to have various yet similar challenges relatives to their sizes. These challenges must be adhered specifically based on the need of these SMEs.